Comparing Efficiency between Dual and Single-Axis Vertical Turbine for Electrical Generating System - Thanutwutthikorn, Kanisorn; Suntivarakorn, Ratchaphol (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 3 (2023): July-September-2023, 2023)
This article reports an efficient comparison between 500W dual and single vertical axis cross-flow turbine for electrical generating systems. The studied parameters were the influence of the distance between dual vertical axes, then, comparing the efficiency with the single cross-flow turbine. From the designation of the L/D ratio as equal to 1, the diameter and height of the dual-axis vertical turbine was 0.3 m while the single-axis vertical turbine was 0.6 m. A chain was used for power transmission with a gear ratio of 1:18 and an induction generator was used as the electrical generating system. The results were that a dual-axis vertical turbine with a 0.8 m water head and at various distances of 3, 6, 9 and 12 cm had an efficiency of 32.36, 28.06, 20.44, and 14.44%, respectively. However, the efficiency decreased with increasing distance between the axes which resulted in a loss of water energy flowing through the axes. The water energy loss was variously 74, 150, 243 and 364 W. In the case of the single-axis vertical turbine, the efficiency was 20.73% which was closes to the dual-axis vertical turbine at a distance of 9 cm. The economic viability of dual-axis vertical turbines is 6.5 years but is 14.77 years for single-axis vertical turbines. Keywords: vertical turbine, cross-flow turbine, electrical generating system